Bridges, brokers and big ideas : a report of the CIC Meeting on the future of Canadian foreign policy - Thompson, Andrew S. (Canadian International Council [S.l.], 2006)
Notes that the common themes that emerged at the meeting, suggest that, despite the major cuts to the country's diplomatic, defence and development programmes in the 1990s, Canada remains uniquely-positioned to make a meaningful difference in the world. Concludes that the challenge for policy-makers is to recognize how it can help most effectively and then to act accordingly.